Coach justice and competence in football - Garcia-Calvo, T.; Leo, F. M.; Gonzáles-Ponce, I. (Football Psychology - From Theory to Practice, 2019)
The ability of a coach to be perceived as fair by players when making decisions is important in the functioning of the team. When a coach makes decisions with a consistent criterion and justification, the players can better understand the actions, behaviours, and attitudes of their coach in situations that can become contentious. In this chapter a theoretical explanation of perceived competence and justice in the head coach will be discussed. Further, the importance of the five coach competence dimensions and the four factors of justice will be analysed. In addition, previous research with business and sports groups will be reviewed, which has shown that perceptions of the different facets of perceived justice influence behaviours and attitudes of members of a group. Finally, selected results with professional football players will be presented. This chapter provides evidence about the emergence of disruptive behaviours of the players towards the coach or to his/her teammates since the perception of unfairness in decision-making within the team can generate unrest and discontent by some team members. Within the study of psychological processes in football, the analysis of coach behaviour has proven to be an essential area due to its importance for the improvement of athlete performance and individual and collective satisfaction of the athletes (Wang & Straub, 2012). This fact has led to an interesting line of research to better understand which variables can optimize players` satisfaction and its derived behavioural benefits, such as higher levels of commitment, effort, or performance (Garcfa-Calvo, Leo, Gonzalez-Ponce, et al., 2014; Myers 8c Feltz, 2012). In this sense, players` perceptions of how coaches impart justice through their decisions and of the competency level of their work are critical constructs that can help to explain players` satisfaction with their coach and their performance on football teams, as well as cohesion, collective efficacy, or motivation. In this chapter, we will identify the characteristics of the perception of coaching competency and justice, the existing measures to evaluate them, and the importance of these variables for a new perspective concerning the analysis of coach behaviour in football. Lastly, we will propose some practical implications that could help professionals improve the application of these variables within the football context.